2022
DOI: 10.12707/rv21043
|View full text |Cite
|
Sign up to set email alerts
|

Fatores que influenciam o uso inadequado do preservativo na perspetiva de jovens universitários

Abstract: Factors influencing condom misuse from the perspective of young university studentsFatores que influenciam o uso inadequado do preservativo na perspetiva de jovens universitários Factores que influyen en el uso inadecuado del preservativo desde la perspectiva de los jóvenes universitarios REVISTA DE ENFERMAGEM REFERÊNCIA homepage: https://rr.esenfc.pt/rr/ ISSNe: 2182.2883

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 10 publications
(28 reference statements)
0
7
0
1
Order By: Relevance
“…Quanto à prática inadequada, verificou-se associação com o relacionamento estável. Diferentes estudos nacionais e internacionais já evidenciaram que o uso do preservativo é menos frequente em pessoas com parcerias fixas (Campos-Rosa et al, 2018;Elshiekh et al, 2020;Oliveira et al, 2022;Petry et al, 2019;Ramos et al, 2020).…”
Section: Discussionunclassified
“…Quanto à prática inadequada, verificou-se associação com o relacionamento estável. Diferentes estudos nacionais e internacionais já evidenciaram que o uso do preservativo é menos frequente em pessoas com parcerias fixas (Campos-Rosa et al, 2018;Elshiekh et al, 2020;Oliveira et al, 2022;Petry et al, 2019;Ramos et al, 2020).…”
Section: Discussionunclassified
“…The second chunk of similarity analysis deepens the context related to sexual practices, where the group demonstrates knowledge about the importance of using condoms as a method of preventing STIs, with emphasis on AIDS and syphilis, possibly because they are the most widespread infections in the media ( 15 - 16 ) .…”
Section: Discussionmentioning
confidence: 99%
“…One of them may be related to the form of contamination, such as sexual violence and rape, which lead people to develop a fear of reporting for reasons related to humiliation, lack of legal knowledge about the act and the feeling of guilt. Another aspect may be related to the fear of rejection by sexual partners and the ability to bear children ( 16 - 17 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Promoting the correct and consistent use of condoms is a significant public health measure to improve sexual and reproductive health (SRH) among young individuals [4]. Several studies have revealed that condom use among higher-education students is inconsistent [5][6][7][8][9][10]. In a Portuguese study on university students' health behaviors, more than half of the participants reported using condoms as a contraceptive method (73.7%), but 31% revealed that they used them inconsistently [11].…”
Section: Introductionmentioning
confidence: 99%
“…The male gender, a more hedonistic and impulsive personality, and beliefs associated with reduced sexual pleasure are identified as the main barriers to effective condom use [17]. Cognitive and psychosocial variables, such as sexual health literacy, a more positive attitude, self-efficacy, and individual commitment to using condoms [18,19], the type of sexual partner, relationship status, and the ability to negotiate condom use with a sexual partner are typically associated with the adoption of the health-promoting behavior of consistent condom use [8,20,21]. Interpersonal influences commonly mediate these predictors, reflecting the importance attributed to significant persons, such as friends, romantic partners, family, and health professionals [19,22].…”
Section: Introductionmentioning
confidence: 99%